The Impact of the COVID-19 Pandemic on the Competitiveness of the Tourism Industry - Paulus Rikumahu (Universitas Gorontalo, 2020)
The COVID-19 pandemic has been going on since December 2019 and changed all predictions of tourism competitiveness in various countries in the world, including various regions in Indonesia. The research objective is intended to measure the competitiveness of tourism in the AmboThe COVID-19 pandemic has been going on since December 2019 and changed all predictions of tourism competitiveness in various countries in the world, including various regions in Indonesia. The research objective is intended to measure the competitiveness of tourism in the Ambon City area to determine the contribution of tourism to the economy of Ambon City and Tual City. This study was done in an exploratory manner. The results of the Competitiveness Monitor analysis show that the competitiveness indicators (Human Tourism, Price Competitiveness, Infrastructure Development, Environment, Human Resources, and Social Development) in Ambon City was better than the ones in Tual City. However, the tourism competitiveness analysis referred to had completely changed along with the regional quarantine (lockdown) system implemented in various countries, and the Regional-Scaled Social Restrictions (Pembatasan Sosial Berskala Regional (PSBR)) system implemented in various provinces in Indonesia – which also included a temporary closure of inter-province seaports in Maluku to limit the virus spread. Therefore, there is an urgency of the role of government and related stakeholders to prepare for a new tourism business order, especially in the provision of transportation, and availability of hotels, restaurants, human resources, and environment which are free from the COVID-19 virus.